Zwicky as a Pluralist - Alan Heiblum Robles (Studia Historiae Scientiarum)
Fritz Zwicky is best known to the general public for his scientific work. His methodological views are less known and some of his philosophical ideas did not receive favorable reviews. In other reading, however, Zwicky’s principle of flexibility of scientific truth, which asserts that no scientific statement can be absolute but rather subject to refinements or expansions, shows it as a contribution to epistemic pluralism.